Gaya Kepemimpinan Transformasional Kepala Sekolah Dasar Di Sukoharjo - Wijaya, Surya (Nur Science Institute, 2023)
Background: This study aims to obtain empirical data on the leadership style of elementary school principals in Sukoharjo Regency in establishing good relationships between teachers and employees. Method: The research method used was qualitative descriptive with data collection techniques through semi-structured interviews and observations. The research informants consisted of principals, teachers, and employees from three different elementary schools. The data analysis process includes data reduction, data presentation, and conclusion drawn. The validity of the data was tested through triangulation of sources and techniques. Result: The results of the study show that school principals in Sukoharjo tend to apply a transformational leadership style in human resource management. This is reflected in efforts to build good interpersonal communication, providing motivation, personal coaching, appreciation for achievements, and active involvement of teachers and employees in the decision-making process. This leadership style has proven to be effective in creating a harmonious work atmosphere and improving the performance of school organizations. Implication: The implications of this study show that transformational leadership styles are relevant to be applied in the context of basic education, particularly in building a collaborative and supportive organizational culture. Principals are advised to continue to develop communication skills, empathy, and motivational skills so that working relationships with teachers and employees can be maintained positively and productively